The isolation of endophytic fungi from plants and the determination of amylase and lipase activities - Samuel Devadasan, Hannah Shobana (2015)
Endophytes refer to a group of microorganisms that are able to grow either intracellularly or intercellularly in plant tissues of higher plants without causing any symptoms or disease in or on those plants. Currently, endophytic fungi are being studied as sources of new enzyme applications. In this project, ten different plant samples were collected from Taman Herba, Universiti Putra Malaysia (UPM). The isolated fungi were screened for the production of extracellular enzymes amylase and lipase. Out of the ten samples which were tested, four samples were further studied, two for each enzyme. Two of the endophytic fungi were identified as Aspergillus sp. and Penicillium sp. respectively. Aspergillus sp is known to have a high amylase activity which explains why the sample which was identified as Aspergillus showed a maximum amylase activity of 0.002 U/ml. The sample identified to produce lipase activity which is Penicilium sp. showed a maximum enzyme activity of 13.5 U/ml. The yield for lipase was much greater than the yield for amylase. The other two samples could not be identified as those fungi are non-spore producing fungi.